[Sans titre] - Fox, Christopher (Circuit, 2005)
A participant at the Darmstadt courses as both a student and teacher between 1982 and 1994, British composer Christopher Fox evokes the many friendships he formed in this place. He describes the vitality of the concerts presented at Darmstadt, including performances of his own music, among others. As a result of his experiences, Fox has written extensively on Darmstadt, with particular attention to the Hommel era, which he witnessed from the beginning.